Religion and emotion : approaches and interpretations - Corrigan, John, 1952- (Oxford University Press, 2004)
Brings together twelve essays in the field of emotion studies. This book examines attitudes toward and expressions of emotion in a range of religious traditions and periods. It provides insights to students of comparative religion, anthropology and psychology.